2010
DOI: 10.1155/2010/864749
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of Sarcomere-to-Membrane Attachment at M-Lines inC. elegansMuscle

Abstract: C. elegans is an excellent model for studying nonmuscle cell focal adhesions and the analogous muscle cell attachment structures. In the major striated muscle of this nematode, all of the M-lines and the Z-disk analogs (dense bodies) are attached to the muscle cell membrane and underlying extracellular matrix. Accumulating at these sites are many proteins associated with integrin. We have found that nematode M-lines contain a set of protein complexes that link integrin-associated proteins to myosin thick filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
(85 reference statements)
1
41
0
Order By: Relevance
“…Many of the proteins of myofilaments, attachment structures, and regulators of contraction/relaxation have been identified through genetic and molecular biological analyses, and characterized cell biologically by using specific antibodies and GFP fusion proteins [Moerman and Fire, 1997; Qadota and Benian, 2010; Gieseler et al, 2016]. For C. elegans muscle, electron microscopy images are also available [Waterston et al, 1980; Zengel and Epstein, 1980; Waterston, 1988; Gieseler et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the proteins of myofilaments, attachment structures, and regulators of contraction/relaxation have been identified through genetic and molecular biological analyses, and characterized cell biologically by using specific antibodies and GFP fusion proteins [Moerman and Fire, 1997; Qadota and Benian, 2010; Gieseler et al, 2016]. For C. elegans muscle, electron microscopy images are also available [Waterston et al, 1980; Zengel and Epstein, 1980; Waterston, 1988; Gieseler et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic tail of integrin is associated with a complex of four conserved proteins (UNC-112 (kindlin), PAT-4 (integrinlinked kinase (ILK) 3 ), PAT-6 (actopaxin), and UNC-97 (PINCH)) (9 -12). UNC-97 links to myosin in thick filaments through four different complexes: via UNC-98, via LIM-9 (FHL) and UNC-96, via LIM-8, and via UNC-95 and LIM-8 (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…During the past decade, at least 10 new sarcomeric proteins have been identified using screens of a yeast 2-hybrid library with baits consisting of known nematode sarcomeric proteins. 17 Homology to vertebrate muscle proteins identify at least another 2 dozen proteins. Thus, the 40 Unc, 20 Pat, 104 sarcomeredefective, 10 interacting, and 24 homologous proteins sum to a total of 198.…”
Section: Proteomes Of Nematodes and Human Heart Are Conservedmentioning
confidence: 99%
“…Nematode muscle M-lines and dense bodies not only serve the function of analogous structures in vertebrate muscle, but also are similar to the costameres of vertebrate striated muscle and the focal adhesions of nonmuscle cells in their anchorage to the plasma membrane and their major proteins ( Figure 2F and Figure 3A and 3B). [15][16][17] Over the past 7 years, it has been reported that multiple protein complexes link the muscle cell membrane to thick filaments at the M-line in C elegans ( Figure 3A). The cytoplasmic tail of integrin is associated with a complex of 4 conserved proteins [UNC-112 (Kindlin in mammals), PAT-4 (integrin linked kinase, ILK), PAT-6 (Actopaxin), and UNC-97 (PINCH)].…”
mentioning
confidence: 99%